Adaesogn Of Retractable Spread Breakers - Ahmad Farhan Iberahim, Ahmad Farhan (Universiti Teknologi Petronas, 2010)
This report concerns with the design of retractable speed breakers. It consists of six chapters that cover the introduction, the project literature review, project methodology, results and discussion, conclusion, references and finally the relevant appendices. The introduction part briefly describes the background study of the problem governing the invention of the speed breakers. It also discussed the problem arose by using the permanent speed breakers and the objective and scope of study of the design of retractable speed breaker. For the second part, the literature review which describe the type of speed breakers and the type of road commonly used. For the third part, the focus is more on the methodology and project work. Then results and discussion discuss about the propose alternative design which can be adopted for the project. It includes drawing and analysis using the Matlab Simulation Tools. The final model and the control mechanism also included. Then several recommendations propose at the end of this report. The project conclusion is also stated in the report together with the references used while doing research work on this project.